Hunger in the Kazakh steppe or “Minor Mistakes” and “Power Shortcomings” - Aldabergenov, К. М. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2018)
In the history of our country the Kazakh people are covered with black cloud after the Dzhungar invasion of the XVIII century, it is the “famine” that devoured two-thirds of the population of 20-30 years of the XX century. Of course, it was written and recorded at the time but many were accused of being “an enemy of the people”. This is evidenced by the “Letter of the five” addressed directly to I.V. Stalin. There are a lot of those who write on this subject: historians, politicians, public figures, writers, journalists. There is also much interest on the part of the readers, viewers and listeners. Such works are interesting not only to regular readers, but also to school and university students, undergraduates, PhD students. Hence, it follows that in the future, having thoroughly studied the “problem of historical white spots,” and having achieved centralized leadership of these processes, we could further help in writing the full history of the Kazakh state. The programs “Manhgilik El” and “Tujan Zher”, which were delivered by the President on the agenda, would be fully implemented. Future generations will proudly remember their history. It says that we can learn a lot from our history. The article examines the main causes of the famine in the Kazakh steppe in 1920-30 of the last century.